Barriers to Care Affecting Presentation to Urogynecologists in a Community Setting. Issue 2 (February 2021) - Smith, Fiona K.; Agu, Ijeoma; Murarka, Shivani; Siddiqui, Gazala; Orejuela, Francisco J.; Muir, Tristi W.; Antosh, Danielle D.
Abstract : Objective: To evaluate barriers to care for patients presenting to urogynecologists and determine how these barriers differ in private and public/county health care settings. Methods: Standardized anonymous questionnaires were distributed from May 2018 to July 2018 to new patients presenting to a urogynecologist at three institutions: two private health care clinics (sites A and B) and one public/county hospital clinic (site C). Patients identified symptom duration, symptom severity, and factors inhibiting presentation to care from a list of barriers. Patients then identified the primary barrier to care. Results: One hundred nine questionnaires were distributed, and 88 were submitted, resulting in an 81% response rate (31 from site A, 30 from site B, 27 from site C). In analysis of the private versus public setting, there was no statistical difference between age (58 years vs 57 years, P = 0.69), body mass index (28 vs 30, P = 0.301), symptom duration (24 months vs 16 months, P = 0.28), or severity respectively. When asked to identify the primary barrier to presentation, patients in the private setting stated they did not know to see a specialist (26.2%, P = 0.002), while patients in the public setting could not obtain a closer appointment time (22.2% vs 13.1%, P = 0.35. Additionally, patients in the public setting were more likely to cite lack of health care coverage as a barrier to care (18.5% vs 1.6%, P = 0.01). Conclusion: This study highlights barriers that can contribute to the disparity of care seen in our patient population. Efforts should be made to acknowledge and mitigate hindrances impacting access to care.